Differential block of U small nuclear ribonucleoprotein particle interactions during in vitro splicing of adenovirus E1A transcripts containing abnormally short introns. - Himmelspach, M (1991)
We have studied the consequences of decreasing the donor site-branch site distance on splicing factor-splice site interactions by analyzing alternative splicing of adenovirus E1A pre-mRNAs in vitro. We show that the proximal 13S donor site has a cis-inhibiting effect on the 9S and 12S mRNA reactions when it is brought too close to the common branch site, suggesting that the factor interactions in the common 3' part of the intron are impaired by the U1 small nuclear ribonucleoprotein particle (snRNP) binding to the displaced 13S donor site. Further analysis of the interactions was carried out by studying complex assembly and the accessibility to micrococcal nuclease digestion of 5'-truncated E1A substrates containing only splice sites for the 13S mRNA reaction. A deletion which brings the donor site- branch site distance to 49 nucleotides, which is just below the minimal functional distance, results in a complete block of the U4-U5-U6 snRNP binding, whereas a deletion 15 nucleotides larger results in a severe inhibition of the formation of the U2 snRNP-containing complexes. Sequence accessibility analyses performed by using the last mini-intron-containing transcript demonstrate that the interactions of U2 snRNP with the branch site are strongly impaired whereas the initial bindings of U1 snRNP to the donor site and of specific factors to the 3' splice site are not significantly modified. Our results strongly suggest that the interaction of U1 snRNP with the donor site of a mini-intron is stable enough in vitro to affect the succession of events leading to U2 snRNP binding with the branch site.